Factor analysis of drop out clients in microfinance institutions (MFIs) in Satkhira district in Bangladesh - Rahman, Muhammad Khalilur; Rahman, Md Moklesur; Jalil, Md Abdul (Canadian Center of Science and Education, 2014)
The main objective of the study is to identify the reasons why clients are dissatisfied and thinking to switch to other MFI or to leave the MFI. A total of 129 valid cases were collected through a random sampling method by means of questionnaires and in-depth interviews, and questions were put to the respondents to measure the levels of satisfaction and dissatisfaction over the MFIs' performance. The data was collected from a regional manager, a branch manager, credit officers and borrowers who were involved in BRAC organization at Satkhira district in Bangladesh, between November 2013 and January 2014. The results revealed that membership cancellation, conflict between medium and small size loan, high interest rate on loan but low on savings, societal facts (e.g. widow, death, unsuitable social role), religion and rude behavior from officers (who collect weekly installments) are substantially very strong which followed by lack of industrial regulatory policy, MFIs considered membership cancellation decision, natural disaster, mistrust and lack of co-operation. The result also found the existence of numerous shortcomings on managerial policy, implementation, infrastructure, organization, system, diplomatic policy, quality service and product facilities the sum total of which cause clients' decision to opt out of the MFIs. The main aspect of the study is that, the results of this study can contribute to improve the management of the business organizations to improvise an effective client-friendly plan in developing microfinance institutions in Bangladesh. The findings of this research may also contribute to the improvement of business organization, especially, the microfinance institutions so that they can satisfactorily serve their clients with the proper facilities, managerial strategy and prudent organizational plan.